2015
DOI: 10.1111/apa.13057
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation is useful in paediatric intensive care units if children are appropriately selected and carefully monitored

Abstract: NIV is useful in PICUs if children are appropriately selected and carefully monitored. Technological advances and future clinical research will improve its use and success rate in PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 54 publications
2
28
0
1
Order By: Relevance
“…The term non‐invasive ventilation (NIV) usually refers to non‐invasive positive pressure ventilation. As a general definition, NIV includes both noninvasive continuous positive airway pressure (CPAP), and non‐invasive intermittent positive pressure ventilation . High‐flow nasal cannula oxygen therapy, although increasingly used, is not considered to be NIV .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The term non‐invasive ventilation (NIV) usually refers to non‐invasive positive pressure ventilation. As a general definition, NIV includes both noninvasive continuous positive airway pressure (CPAP), and non‐invasive intermittent positive pressure ventilation . High‐flow nasal cannula oxygen therapy, although increasingly used, is not considered to be NIV .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the paucity of randomized controlled trials (RCT) about its efficacy as a first‐line mode of mechanical ventilation in children, clinical evidence of the usefulness of NIV has led to a wide acceptance to treat several pathologies . Consequently, it has been reported that the use of NIV has significantly increased during the past two decades . The use of NIV has also spread outside intensive care units …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noninvasive ventilation (NIV) is a treatment for patients with respiratory dysfunction accomplished by an external interface and a positive pressure ventilator [1]. NIV has been applying increasingly in pediatric patients with acute respiratory failure of various etiologies.…”
Section: Introductionmentioning
confidence: 99%